Correlation of serum tryptase levels with total number of nevi, Breslow thickness, ulceration, and mitotic index in melanoma patients: evaluation of a promising prognostic marker. Issue 6 (December 2019) - Crincoli, Emanuele; Moliterni, Elisa; Catania, Fiammetta; Didona, Dario; Calvieri, Stefano; Paolino, Giovanni
Abstract : Current evidences suggest that mast cells contribute to the proliferation and differentiation of skin melanocytes. According to these findings, we carried out an observational cross-sectional study to investigate the correlation between the total number of nevi (TN), Breslow thickness (BT), and serum tryptase (ST) levels in a cohort of 35 melanoma (MM) patients. A Mann–Whitney test was performed to compare ST values within each variable. Subsequently, the independent predictive factors were assessed by multiple logistic regression. Pearson's χ 2 -test was chosen to detect statistically significant findings on the TN and the histopatological variables (Breslow, ulceration, and mitotic index). The TN was assessed using a dichotomous scale (⩽ 10 or > 10). Patients with TN of 10 or less (3.48 vs. 6.05 ng/ml; P = 0.045), patients with a Breslow thickness of at least 1.01 mm (2.99 vs. 5.67 ng/ml; P = 0.1), and ulcerated MM (2.37 vs. 6.05 ng/ml; P < 0.001) showed lower median ST levels. Similarly, MM with mitotic index of at least 1/mm 2 had median ST levels lower than MM with mitotic index less than 1/mm 2 ( P = 0.005). Multiple logistic regression confirmed the statistical significance for the variables ulceration, TN, and mitotic index. Pearson's χ 2 -test showed a statistically significantly ( P = 0.003) increased prevalence of MMs with a BT of at least 1.01 mm in patients with a TN of 10 or less. Patients with a TN of 10 or less also showed a higher prevalence of ulceration and mitotic index of at least 1/mm 2 in comparison with the rest of the cohort. Our study highlights lower median ST levels in patients whose MM thickness is at least 1.01 mm; this may encourage new studies on the role of ST in MM also according to the number of nevi.